Ethics and Epidemiology 2009
DOI: 10.1093/acprof:oso/9780195322934.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Public Health Practice

Abstract: This chapter outlines a perspective that can serve as a foundation for addressing ethical concerns in public health practice. It argues that ethics in public health practice is shaped by the mission of public health and that the ethical obligations of public health practitioners are grounded in their commitment to that mission and in their voluntary assumption of responsibility for the public's health. Society also has an interest in the public's health and that endorsement provides partial justification for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The formal principle of justice demands that ‘equals should be treated equally’ and that benefits and costs or harms are fairly distributed or received. 1 Questions considering how equality is determined or characterised, and whether it is in fact realistic to attempt to treat people equally, have led to the development of numerous competing and distinct theories. 17 Within egalitarian theories, the concept of fair opportunity and unfair discrimination is founded on the premise that to base actions or policies on differences that the affected individual has no control over is not acceptable.…”
Section: Principlism and The Ethics Of Contact Precautionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formal principle of justice demands that ‘equals should be treated equally’ and that benefits and costs or harms are fairly distributed or received. 1 Questions considering how equality is determined or characterised, and whether it is in fact realistic to attempt to treat people equally, have led to the development of numerous competing and distinct theories. 17 Within egalitarian theories, the concept of fair opportunity and unfair discrimination is founded on the premise that to base actions or policies on differences that the affected individual has no control over is not acceptable.…”
Section: Principlism and The Ethics Of Contact Precautionsmentioning
confidence: 99%
“…The need for more research into a range of infection prevention and control challenges has been suggested, 30,65 67 and it is recognised that a reliance on quantitative methods to measure the effectiveness of Contact Precautions without qualitatively considering the impact on the lives of affected people fails to acknowledge and respect the integrity of the community and its autonomy. 1 Further qualitative analysis of the ethical issues surrounding the application of Contact Precautions would support a more holistic understanding of the topic.…”
Section: Principlism and The Ethics Of Contact Precautionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between research and public health practice has rather a legal and institutional than essential character (E10). Some suggest that in case of doubt, whether a certain activity constitutes research or practice the question should be answered by an IRB/REC (McKeown and Leaner 2009 ).…”
Section: Resultsmentioning
confidence: 99%